2015
DOI: 10.4172/2157-7579.1000329
|View full text |Cite
|
Sign up to set email alerts
|

Use of Native Bovine Bone Morphogenetic Protein Extract in Healing Segmental Tibial Bone Defects in Goats

Abstract: We tested the new bone-forming activity of injectable native bovine BMP extracted from cadaveric bones obtained from the abattoir after SDS PAGE electrophoresis was used to determine the molecular weights and extract was bio-assayed in the goat thigh muscle pouch model. The bovine BMP extract was further used as an implant in an absorbable collagen sponge (ACS) and hydroxyapatite to heal segmental bone defects in a large animal tibia fracture model. Open tibia fractures were created in 20 adult goats with loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Since fracture healing involves a local cascade of molecular and cellular events, targeting the fracture environment systemically has not been reproduced successful (Harris et al, 1975, Moskilde & Bak 1993. Local injection of various growth factors other than BMPs has produced mixed results (Uwagie-Ero et al, 2014;Adeyanju et al, 1982;Joyce et al, 1990;Nash et al, 1994;Bland et al, 1995) and other studies have shown the successful use of rhBMP-2 with various carriers to heal large segmental bone defects, enhance periodontal regeneration, and promote spinal fusion (Uwagie-Ero et al, 2016;Gerhart et al, 1993, Cook et al, 1994a. For effective delivery of growth factors into a fracture or segmental bone defect, biological carriers are required to prevent rapid dispersion of the proteins (Cook et al, 1994b;Sandhu et al, 1995;Wang et al 1998) and prolong the exposure time of the growth factor to osteoprogenitor cells hydroxyapatite was used as a carrier in this study and it served as a suitable biocarrier for BMP.…”
Section: Discussionmentioning
confidence: 99%
“…Since fracture healing involves a local cascade of molecular and cellular events, targeting the fracture environment systemically has not been reproduced successful (Harris et al, 1975, Moskilde & Bak 1993. Local injection of various growth factors other than BMPs has produced mixed results (Uwagie-Ero et al, 2014;Adeyanju et al, 1982;Joyce et al, 1990;Nash et al, 1994;Bland et al, 1995) and other studies have shown the successful use of rhBMP-2 with various carriers to heal large segmental bone defects, enhance periodontal regeneration, and promote spinal fusion (Uwagie-Ero et al, 2016;Gerhart et al, 1993, Cook et al, 1994a. For effective delivery of growth factors into a fracture or segmental bone defect, biological carriers are required to prevent rapid dispersion of the proteins (Cook et al, 1994b;Sandhu et al, 1995;Wang et al 1998) and prolong the exposure time of the growth factor to osteoprogenitor cells hydroxyapatite was used as a carrier in this study and it served as a suitable biocarrier for BMP.…”
Section: Discussionmentioning
confidence: 99%